How social capital matters for receiving social support: on the complementary role of civil society in the COVID-19 pandemic - Gesine Höltmann; Swen Hutter; Jule Specht (European Societies, 2023)
The Covid-19 pandemic has created a widespread need for social support. Similar to previous crises, we can observe activation in society to meet these needs: citizens have offered practical, emotional, and financial support, often within their social networks, but also to strangers and civil society organizations. In this paper, we examine the role of social capital in receiving social support during the Covid-19 pandemic in Germany using unique microlevel survey data. We investigate the importance of three aspects of social capital – the size of one's support network, social trust, and organizational memb ership – for receiving (sufficient) social support. We focus on three types of support networks: family and friends, neighbors, and civil society actors. First, we find that while all three elements of social capital matter for receiving social support, a larger support network and organizational embeddedness matter primarily for receiving support beyond family and friendship networks. Second, civil society actors have been less likely to provide sufficient support in the pandemic, mainly acting in addition to strong ties and providing complementary support for individuals in particular need.
Keywords: 300; Social capital; social support; social trust; civic engagement; civil society; coronavirus crisis; COVID-19